ANALISIS KEAMANAN WEB NEW KUTA GOLF MENGGUNAKAN METODE VULNERABILITY ASSESSMENTS DAN PERHITUNGAN SECURITY METRIKS - Rifky Lana Rahardian (Jurnal Informatika Dan Tekonologi Komputer (JITEK), 2022)
Various crimes that are security threats that can occur when we are socially networked, one of them is virtual theft. New Kuta Golf has tournament standard field and the first course with a layout model link. Large mobility companies also make data processing even bigger and more web sites that are concerned with transactions and promotional media. This is a reference to obtain information about the security of the New Kuta Golf website. The data that has been obtained are carried out for the project work step, are: (1) To conduct a Vulnerability assessment. (2) Analyze the results of the scan. (3) Calculate security metrics from the results obtained from the scanning process. (4) Documentation of the installation process, and calculating security metrics. The results of the research then analyzed and discussed with a review of the theory that was embraced. From the results of the tests, the following results are obtained: (1) In carrying out website security testing can be done by Vulnerability Assessment uses the acunetix application to find detailed results. (2) Determining the security of a website can be determined using security metrics. (3) The results of the vulnerability assessment on http://newkutagolf.co.id has a high value.